Development of the Digital Field Experience Model to Engage Adult Extension Audiences Synchronously Online - Peyton N. Beattie; Jamie Loizzo; Matt Benge; Glenn D. Israel; Tracy Irani; Nick T Place (Journal of Applied Communications, 2024)
Mobile technologies and the internet have greatly influenced how people create and consume information and the design and implementation of learning environments. Prior research indicated land grant universities should continue to adapt to the evolving Information Age, train Extension professionals to use ICTs, and leverage ICTs for innovative communication and education with diverse audiences to remain credible and relevant. The following professional development article introduces the digital field experience (DFE) model to engage adult Extension audiences through digital programs. The DFE parameters included: (a) digital delivery of the experience; (b) a component which must include a synchronous, live field experience; and (c) designed for adults as the target audience. In a pilot program, the lead author taught three UF/IFAS Extension agents about DFEs, adult learning, instructional design, and instructional and communication technologies. Throughout the training program the Extension agents developed and delivered their own DFE. The observational outcomes of the DFEs are shared below. The Extension agents adapted the content and the format of the DFE to fit their respective Extension programs, which included a cooking demonstration, the importance of beetles in the landscape, and a virtual beehive tour. Overall, the Extension agents seemed to be pleased with and excited about the experience. A digital experience with a live, hands-on (as they referred to it) component was something that they had been wanting to venture out and try, but they had not committed to doing yet.
Keywords: digital field experience; instructional and communication technologies; Extension